Wave 2 weighting and non-response - Sipthorp, M; Misson, S (My University, 2007)
This paper details the methodology used to calculate the weights for the Wave 2 sample of Growing Up in Australia, the Longitudinal Study of Australian Children (LSAC). During 2004, the study recruited a nationally representative sample of 5,107 0-1 year olds (B-cohort) and 4,983 children aged 4-5 years (K-Cohort) selected from the Medicare enrolments database. Weights in the LSAC data set in Wave 1 were used to provide some measure of correction unequal probability of selection and non-response of potential respondents. This paper discusses the calculation of Wave 2 weights, non-response to forms, response rates for sub-populations, and dDescriptive statistics for predictor variables of non-response by response status and cohort.
5
Technical paper
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology